Preparation technology of anti-corrosion coating for sulfuric acid contact parts
Through a process of anti-corrosion coating preparation for sulfuric acid contacts including chemical oxidation treatment, single-molecular layer formation and modified powder, the problem of poor corrosion resistance and prone to failure at high temperatures is solved, and efficient anti-corrosion effect and long-term protection effect are achieved.
Patent Information
- Application Number
- CN202411812997.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-11
AI Technical Summary
In the prior art, the coating of sulfuric acid contacts has poor corrosion resistance and is prone to failure at high temperatures, so it cannot effectively deal with the corrosion problem of sulfuric acid.
A sulfuric acid contact anti-corrosion coating preparation process is adopted, including chemical oxidation treatment, the use of 3-aminopropyltriethoxysilane solution to form a single molecule layer, the synthesis of modified powder A and powder B, and dispersed in N,N-dimethylformamide, and sprayed onto the surface of the sulfuric acid contact after ultrasonic treatment.
It realizes the high corrosion resistance of sulfuric acid contact coating, can maintain reliability in a high temperature and high concentration reaction environment, and extend the service life of metal materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of anti-corrosion coatings, and in particular, relates to a process for preparing an anti-corrosion coating for a sulfuric acid contact part. Background Art
[0002] Sulfuric acid is a colorless, oily liquid with strong water absorption and corrosiveness. In the chemical industry, sulfuric acid is one of the most widely used chemicals, and its importance cannot be underestimated. First of all, as a strong acid, sulfuric acid acts as a catalyst in chemical reactions, which can accelerate or promote the progress of various chemical reactions. For example, in the process of oil refining, sulfuric acid is used in processes such as desulfurization and dewaxing to ensure that the quality of petroleum products meets the standards. In addition, sulfuric acid is also widely used in fertilizer production, such as the manufacture of phosphate fertilizers, by reacting with phosphate ore to produce phosphoric acid, and then making various phosphate fertilizers. Sulfuric acid also has important applications in the pharmaceutical industry. In the synthesis process of many drugs, sulfuric acid needs to be used as a catalyst or reaction medium to improve the selectivity and yield of the reaction. For example, in the process of producing aspirin, sulfuric acid as a catalyst promotes the esterification reaction of salicylic acid and acetic anhydride. In addition, sulfuric acid also plays a key role in many fields such as dyes, pigments, plastics, and textiles, providing the necessary chemical raw materials and support for the production of these industries.
[0003] However, although sulfuric acid plays an indispensable role in chemical production, its strong corrosiveness also poses serious challenges to production and equipment. Sulfuric acid not only has a strong ability to corrode metal materials, but also can destroy non-metallic materials, leading to equipment damage, reduced production efficiency and even safety accidents. Therefore, how to effectively deal with the corrosion problem of sulfuric acid has become one of the key technical problems that need to be solved in chemical production. The corrosion of sulfuric acid on metal materials can be divided into two categories: uniform corrosion and local corrosion. Uniform corrosion refers to the uniform chemical reaction between sulfuric acid and the metal surface, causing the metal to gradually become thinner. This type of corrosion usually occurs in a low-concentration sulfuric acid environment. As the concentration increases, the corrosion rate will gradually decrease, but under certain specific conditions, such as high temperature and high pressure environments, the corrosion rate may suddenly accelerate. Local corrosion is more serious. It includes pitting, crevice corrosion and stress corrosion cracking. These forms of corrosion often cause structural damage such as perforation and cracking in the equipment, seriously affecting the service life and safety of the equipment.
[0004] Specifically for different materials, carbon steel is one of the most commonly used materials, but due to its low corrosion resistance, it is prone to rapid corrosion in sulfuric acid environments. Although stainless steel has good corrosion resistance, it can also be affected by pitting and crevice corrosion under certain conditions. Titanium and titanium alloys show excellent corrosion resistance in most sulfuric acid environments, but the cost is high and corrosion may still occur at high temperatures. In addition, although non-metallic materials such as glass, ceramics and plastics can replace metal materials in some cases, their mechanical strength and thermal stability are relatively poor and are not suitable for use in high temperature and high pressure environments.
[0005] These corrosion problems will not only lead to early failure of equipment, increase the cost of maintenance and replacement, but also cause production interruptions, affecting the economic benefits of the enterprise. More seriously, the corrosion of equipment may lead to leakage accidents, which not only pollute the environment, but also may cause major safety accidents such as fire and explosion. Therefore, how to effectively solve the corrosion problem of sulfuric acid has become an important issue that needs to be solved in chemical production.
[0006] In response to the corrosion problem of sulfuric acid contact parts, the chemical industry has currently adopted a variety of methods to improve the corrosion resistance of equipment, mainly including technical means such as material selection, surface treatment and protective coating. Protective coating is another effective anti-corrosion method. By coating a layer of corrosion-resistant material on the metal surface, a physical barrier is formed to prevent sulfuric acid from directly contacting the substrate. Common protective coating materials include organic coatings such as epoxy resins, polyurethanes and fluorine coatings and inorganic coatings such as silicate and phosphate coatings. However, the coatings in the prior art still have the problems of poor anti-corrosion performance and easy failure over time. Summary of the invention
[0007] In order to solve the problem in the prior art that the sulfuric acid contact piece coating has poor corrosion resistance and is easy to fail at high temperature, the present application provides a process for preparing an anti-corrosion coating for sulfuric acid contact pieces. The obtained sulfuric acid contact piece coating has strong corrosion resistance and long service life, and can still ensure the reliability of the contact piece in a high temperature and high concentration reaction environment.
[0008] A process for preparing an anti-corrosion coating for a sulfuric acid contact part comprises the following steps:
[0009] S1. Perform chemical oxidation treatment on the sulfuric acid contact parts and soak them in the treatment solution at room temperature for 10-20 minutes;
[0010] S2. Add 3-aminopropyltriethoxysilane to anhydrous ethanol and stir until completely dissolved. Soak the sulfuric acid contact parts after chemical oxidation treatment in the above solution, let it stand at room temperature for 12-16 hours, take it out, and rinse it with anhydrous ethanol for later use.
[0011] S3, dissolving 2-methylimidazole and zinc nitrate hexahydrate in deionized water respectively, slowly adding the 2-methylimidazole solution to the zinc nitrate solution, stirring for 30-40 minutes, heating to 100-120°C for reaction for 20-24 hours, cooling to room temperature after the reaction, collecting the precipitate by centrifugation, washing with deionized water and anhydrous ethanol respectively, vacuum drying for 12-16 hours to obtain a powder, and then dispersing the powder in N,N-dimethylformamide, ultrasonically treating for 30-40 minutes, and then adding 3-aminopropyltriethoxysilane, continuing ultrasonic treatment for 1-2 hours, washing with N,N-dimethylformamide and drying for 12-16 hours to obtain a modified powder A;
[0012] S4, dissolving acrylic acid and azobisisobutyronitrile in anhydrous ethanol, reacting for 5-7 hours at 65-75° C. in a nitrogen atmosphere, cooling to room temperature, collecting the precipitate by centrifugation, washing with anhydrous ethanol and drying for 12-16 hours to obtain powder B;
[0013] S5. Disperse the modified powder A obtained in S3 and the powder B obtained in S4 in N,N-dimethylformamide, perform ultrasonic treatment for 30-50 minutes, add ethanol, and obtain a sulfuric acid contact part anti-corrosion coating slurry.
[0014] Furthermore, the sulfuric acid contact parts were pre-treated by ultrasonic cleaning with anhydrous ethanol and acetone for 10-20 minutes respectively.
[0015] Furthermore, the treatment liquid in step S1 is one or more of hydrochloric acid, sodium hydroxide, sulfuric acid or nitric acid, with a concentration of 5%-10%.
[0016] Furthermore, the concentration of the 3-aminopropyltriethoxysilane solution in step S2 is 0.07-0.15 mol / L.
[0017] Furthermore, in step S3, the concentration of the 2-methylimidazole solution is 0.25-0.35 mol / L, and the concentration of the zinc nitrate solution is 0.02-0.05 mol / L.
[0018] Furthermore, the mass ratio of the powder in step S3 to 3-aminopropyltriethoxysilane is 2-5:1.
[0019] Furthermore, in step S4, the mass ratio of acrylic acid to azobisisobutyronitrile is 45-55:1.
[0020] Furthermore, in step S5, the weight ratio of the modified powder A to the powder B is 1-3:1.
[0021] Furthermore, the sulfuric acid contact piece anti-corrosion coating slurry is sprayed onto the surface of the sulfuric acid contact piece, dried at room temperature for 1-2 hours, and then placed in an oven, heated to 70-90° C., and cured for 2-4 hours.
[0022] Furthermore, the spraying thickness of the sulfuric acid contact part anti-corrosion coating slurry is 10-15 μm.
[0023] The beneficial effects of this application are:
[0024] Surface pretreatment has a significant effect on the deposition and corrosion performance of magnesium alloy surface coatings. Appropriate pretreatment can improve the adhesion and anti-corrosion performance of the coating. The pretreated metal sample was immersed in a 3-aminopropyltriethoxysilane solution and left at room temperature for 12 hours, so that the monolayer spontaneously formed a dense protective layer on the metal surface, providing a preliminary physical barrier and reducing the direct contact between the corrosive medium and the metal surface. 3-Aminopropyltriethoxysilane may form a dense monolayer on the metal surface through chemical bonding. This chemical bonding not only provides strong adhesion, but also makes the monolayer highly stable and uniform on the metal surface. During the formation process, the molecules will spontaneously arrange into an ordered structure to form a highly regular monolayer. This orderly arrangement makes the monolayer highly hydrophobic and has a low surface energy, thereby effectively reducing the contact between the corrosive medium and the metal surface.
[0025] Modified powder A has a high specific surface area and porosity, but the inventors found that its pore size is moderate, which can effectively capture corrosive media, thereby reducing the erosion of corrosive media on the metal surface, and can maintain its own structural stability by releasing part of the media after adsorbing the corrosive media. This structural stability enables the coating to provide continuous protection for a long time and will not lose its protective effect due to changes in environmental conditions. Polyacrylic acid is a pH-sensitive polymer, and its structure changes under different pH environments. In a neutral or weakly acidic environment, polyacrylic acid maintains a stable structure. When the environmental pH value decreases, polyacrylic acid will swell or cross-link to form a denser protective layer. This structural change may be due to the ionization of the carboxyl groups in the polyacrylic acid molecules under different pH environments. Through the composite action of modified powder A and polyacrylic acid, more comprehensive protection is provided to jointly resist the erosion of corrosive media. Under acidic conditions, the carboxyl groups in polyacrylic acid may be partially protonated to form more carboxylates. These protonated carboxyl groups can form stronger interactions with other carboxyl groups or metal centers on the surface of modified powder A, which in turn promote the cross-linking of polyacrylic acid. This cross-linking effect can enhance the overall structural stability of the coating, thereby providing continuous protection and extending the service life of the metal material. The coating provided in this application is suitable for a variety of metal substrates, including magnesium alloys, aluminum alloys, stainless steel and copper, and has a wide range of applicability. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.
[0027] The equipment used in the preparation method of the present invention can be the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified.
[0028] Example 1
[0029] S1. Ultrasonic clean the 304 stainless steel sulfuric acid contact parts with anhydrous ethanol and acetone for 10 minutes respectively to remove grease and impurities on the surface. Chemically oxidize the stainless steel sulfuric acid contact parts, soak them in 10% sulfuric acid at room temperature for 10 minutes, rinse them with deionized water, and dry them for later use.
[0030] S2. Add 0.6 g of 3-aminopropyltriethoxysilane to 20 mL of anhydrous ethanol and stir until completely dissolved. Soak the sulfuric acid contact parts after chemical oxidation treatment in the above solution, let it stand at room temperature for 12 hours, then take it out, rinse it with anhydrous ethanol three times, and dry it for later use.
[0031] S3. Dissolve 0.5 g of 2-methylimidazole and 0.2 g of zinc nitrate hexahydrate in 20 mL of deionized water, slowly add the 2-methylimidazole solution dropwise to the zinc nitrate solution, stir thoroughly for 30 minutes, heat to 120 ° C and react for 24 hours. After the reaction is completed, cool to room temperature, collect the precipitate by centrifugation, wash it with deionized water and anhydrous ethanol for 3 times, vacuum dry it for 12 hours to obtain powder, then disperse 0.1 g of the powder in 50 mL of N, N-dimethylformamide, ultrasonically treat it for 30 minutes, then add 0.05 g of 3-aminopropyltriethoxysilane, continue ultrasonic treatment for 1 hour, wash it with N, N-dimethylformamide 3 times and dry it for 12 hours to obtain modified powder A.
[0032] S4. Dissolve 0.5 g of acrylic acid and 0.01 g of azobisisobutyronitrile in 50 mL of anhydrous ethanol, react at 70°C for 6 hours under a nitrogen atmosphere, then cool to room temperature, collect the precipitate by centrifugation, wash it three times with anhydrous ethanol, and dry it for 12 hours to obtain powder B.
[0033] S5. Disperse 0.1 g of modified powder A obtained from S3 and 0.1 g of powder B obtained from S4 in 50 mL of N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes, add 50 mL of ethanol, and obtain a sulfuric acid contact part anti-corrosion coating slurry.
[0034] S6. Spray the sulfuric acid contact part anti-corrosion coating slurry onto the surface of the sulfuric acid contact part, dry it at room temperature for 1 hour, put it into an oven, heat it to 80°C, and cure it for 2 hours.
[0035] Example 2
[0036] S1. Ultrasonic clean the stainless steel sulfuric acid contact parts with anhydrous ethanol and acetone for 20 minutes respectively to remove grease and impurities on the surface. Chemically oxidize the stainless steel sulfuric acid contact parts by soaking them in 10% sulfuric acid at room temperature for 20 minutes, rinse them with deionized water, and dry them for later use.
[0037] S2. Add 0.3 g of 3-aminopropyltriethoxysilane to 20 mL of anhydrous ethanol and stir until completely dissolved. Soak the sulfuric acid contact parts after chemical oxidation treatment in the above solution, let it stand at room temperature for 16 hours, then take it out, rinse it with anhydrous ethanol for 3 times, and dry it for later use.
[0038] S3. Dissolve 0.32 g of 2-methylimidazole and 0.29 g of zinc nitrate hexahydrate in 20 mL of deionized water, slowly add the 2-methylimidazole solution dropwise to the zinc nitrate solution, stir thoroughly for 30 minutes, heat to 100 ° C and react for 20 hours. After the reaction is completed, cool to room temperature, collect the precipitate by centrifugation, wash it with deionized water and anhydrous ethanol for 3 times, vacuum dry it for 16 hours to obtain a powder, then disperse 0.25 g of the powder in 50 mL of N, N-dimethylformamide, ultrasonically treat it for 30 minutes, then add 0.05 g of 3-aminopropyltriethoxysilane, continue ultrasonic treatment for 2 hours, wash it with N, N-dimethylformamide 3 times and dry it for 16 hours to obtain modified powder A.
[0039] S4. Dissolve 0.45 g of acrylic acid and 0.01 g of azobisisobutyronitrile in 50 mL of anhydrous ethanol, react at 65°C for 5 hours under a nitrogen atmosphere, then cool to room temperature, collect the precipitate by centrifugation, wash it three times with anhydrous ethanol, and dry it for 16 hours to obtain powder B.
[0040] S5. Disperse 0.3 g of modified powder A obtained from S3 and 0.1 g of powder B obtained from S4 in 50 mL of N,N-dimethylformamide, perform ultrasonic treatment for 50 minutes, add 50 mL of ethanol, and obtain a sulfuric acid contact part anti-corrosion coating slurry.
[0041] S6. Spray the sulfuric acid contact part anti-corrosion coating slurry onto the surface of the sulfuric acid contact part, dry it at room temperature for 1 hour, put it into an oven, heat it to 70°C, and cure it for 4 hours.
[0042] Example 3
[0043] S1. Ultrasonic clean the stainless steel sulfuric acid contact parts with anhydrous ethanol and acetone for 15 minutes respectively to remove grease and impurities on the surface. Chemically oxidize the stainless steel sulfuric acid contact parts by soaking them in 10% sulfuric acid at room temperature for 15 minutes, rinse them with deionized water, and dry them for later use.
[0044] S2. Add 0.4 g of 3-aminopropyltriethoxysilane to 20 mL of anhydrous ethanol and stir until completely dissolved. Soak the sulfuric acid contact parts after chemical oxidation treatment in the above solution, let it stand at room temperature for 16 hours, then take it out, rinse it with anhydrous ethanol three times, and dry it for later use.
[0045] S3. Dissolve 0.41 g of 2-methylimidazole and 0.17 g of zinc nitrate hexahydrate in 20 mL of deionized water, slowly add the 2-methylimidazole solution dropwise to the zinc nitrate solution, stir thoroughly for 35 minutes, heat to 110°C for reaction for 22 hours, cool to room temperature after the reaction, collect the precipitate by centrifugation, wash it three times with deionized water and anhydrous ethanol, respectively, and vacuum dry it for 14 hours to obtain a powder, then disperse 0.15 g of the powder in 50 mL of N,N-dimethylformamide, ultrasonically treat it for 30 minutes, then add 0.05 g of 3-aminopropyltriethoxysilane, continue ultrasonic treatment for 1.5 hours, wash it three times with N,N-dimethylformamide and dry it for 14 hours to obtain a modified powder A.
[0046] S4. Dissolve 0.55 g of acrylic acid and 0.01 g of azobisisobutyronitrile in 50 mL of anhydrous ethanol, react at 75 °C for 6 hours under a nitrogen atmosphere, then cool to room temperature, collect the precipitate by centrifugation, wash it three times with anhydrous ethanol, and dry it for 14 hours to obtain powder B.
[0047] S5. Disperse 0.2 g of modified powder A obtained from S3 and 0.1 g of powder B obtained from S4 in 50 mL of N,N-dimethylformamide, perform ultrasonic treatment for 50 minutes, add 50 mL of ethanol, and obtain a sulfuric acid contact part anti-corrosion coating slurry.
[0048] S6. Spray the sulfuric acid contact part anti-corrosion coating slurry onto the surface of the sulfuric acid contact part, dry it at room temperature for 1.5 hours, put it into an oven, heat it to 90°C, and cure it for 3 hours.
[0049] Comparative Example 1
[0050] S1. Ultrasonic clean the stainless steel sulfuric acid contact parts with anhydrous ethanol and acetone for 10 minutes respectively to remove grease and impurities on the surface. Chemically oxidize the stainless steel sulfuric acid contact parts by soaking them in 10% sulfuric acid at room temperature for 10 minutes, rinse them with deionized water, and dry them for later use.
[0051] S2. Dissolve 0.5 g of 2-methylimidazole and 0.2 g of zinc nitrate hexahydrate in 20 mL of deionized water, slowly add the 2-methylimidazole solution dropwise to the zinc nitrate solution, stir thoroughly for 30 minutes, heat to 120°C for reaction for 24 hours, cool to room temperature after the reaction, collect the precipitate by centrifugation, wash it three times with deionized water and anhydrous ethanol, respectively, and vacuum dry it for 12 hours to obtain a powder, then disperse 0.1 g of the powder in 50 mL of N,N-dimethylformamide, ultrasonically treat it for 30 minutes, then add 0.05 g of 3-aminopropyltriethoxysilane, continue ultrasonic treatment for 1 hour, wash it three times with N,N-dimethylformamide and dry it for 12 hours to obtain a modified powder A.
[0052] S3. Dissolve 0.5 g of acrylic acid and 0.01 g of azobisisobutyronitrile in 50 mL of anhydrous ethanol, react at 70°C for 6 hours under a nitrogen atmosphere, then cool to room temperature, collect the precipitate by centrifugation, wash it three times with anhydrous ethanol, and dry it for 12 hours to obtain powder B.
[0053] S4. Disperse 0.1 g of modified powder A obtained from S2 and 0.1 g of powder B obtained from S3 in 50 mL of N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes, and add 50 mL of ethanol to obtain a sulfuric acid contact part anti-corrosion coating slurry.
[0054] S5. Spray the sulfuric acid contact part anti-corrosion coating slurry onto the surface of the sulfuric acid contact part, dry it at room temperature for 1 hour, put it into an oven, heat it to 80°C, and cure it for 2 hours.
[0055] Comparative Example 2
[0056] S1. Ultrasonic clean the stainless steel sulfuric acid contact parts with anhydrous ethanol and acetone for 10 minutes respectively to remove grease and impurities on the surface. Chemically oxidize the stainless steel sulfuric acid contact parts by soaking them in 10% sulfuric acid at room temperature for 10 minutes, rinse them with deionized water, and dry them for later use.
[0057] S2. Add 0.6 g of 3-aminopropyltriethoxysilane to 20 mL of anhydrous ethanol and stir until completely dissolved. Soak the sulfuric acid contact parts after chemical oxidation treatment in the above solution, let it stand at room temperature for 12 hours, then take it out, rinse it with anhydrous ethanol three times, and dry it for later use.
[0058] S3. Dissolve 0.5 g of acrylic acid and 0.01 g of azobisisobutyronitrile in 50 mL of anhydrous ethanol, react at 70°C for 6 hours under a nitrogen atmosphere, then cool to room temperature, collect the precipitate by centrifugation, wash it three times with anhydrous ethanol, and dry it for 12 hours to obtain powder B.
[0059] S4. Disperse 0.1 g of powder B obtained in S3 in 50 mL of N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes, and add 50 mL of ethanol to obtain a slurry for corrosion protection coating of sulfuric acid contact parts.
[0060] S5. Spray the sulfuric acid contact part anti-corrosion coating slurry onto the surface of the sulfuric acid contact part, dry it at room temperature for 1 hour, put it into an oven, heat it to 80°C, and cure it for 2 hours.
[0061] Comparative Example 3
[0062] S1. Ultrasonic clean the stainless steel sulfuric acid contact parts with anhydrous ethanol and acetone for 10 minutes respectively to remove grease and impurities on the surface. Chemically oxidize the stainless steel sulfuric acid contact parts by soaking them in 10% sulfuric acid at room temperature for 10 minutes, rinse them with deionized water, and dry them for later use.
[0063] S2. Add 0.6 g of 3-aminopropyltriethoxysilane to 20 mL of anhydrous ethanol and stir until completely dissolved. Soak the sulfuric acid contact parts after chemical oxidation treatment in the above solution, let it stand at room temperature for 12 hours, then take it out, rinse it with anhydrous ethanol three times, and dry it for later use.
[0064] S3. Dissolve 0.5 g of 2-methylimidazole and 0.2 g of zinc nitrate hexahydrate in 20 mL of deionized water, slowly add the 2-methylimidazole solution dropwise to the zinc nitrate solution, stir thoroughly for 30 minutes, heat to 120 ° C and react for 24 hours. After the reaction is completed, cool to room temperature, collect the precipitate by centrifugation, wash it with deionized water and anhydrous ethanol for 3 times, vacuum dry it for 12 hours to obtain powder, then disperse 0.1 g of the powder in 50 mL of N, N-dimethylformamide, ultrasonically treat it for 30 minutes, then add 0.05 g of 3-aminopropyltriethoxysilane, continue ultrasonic treatment for 1 hour, wash it with N, N-dimethylformamide 3 times and dry it for 12 hours to obtain modified powder A.
[0065] S4. Disperse 0.1 g of the modified powder A obtained in S3 in 50 mL of N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes, and add 50 mL of ethanol to obtain a sulfuric acid contact part anti-corrosion coating slurry.
[0066] S5. Spray the sulfuric acid contact part anti-corrosion coating slurry onto the surface of the sulfuric acid contact part, dry it at room temperature for 1 hour, put it into an oven, heat it to 80°C, and cure it for 2 hours.
[0067] Comparative Example 4
[0068] S1. Ultrasonic clean the stainless steel sulfuric acid contact parts with anhydrous ethanol and acetone for 10 minutes respectively to remove grease and impurities on the surface. Chemically oxidize the stainless steel sulfuric acid contact parts by soaking them in 10% sulfuric acid at room temperature for 10 minutes, rinse them with deionized water, and dry them for later use.
[0069] S2. Add 0.6 g of 3-aminopropyltriethoxysilane to 20 mL of anhydrous ethanol and stir until completely dissolved. Soak the sulfuric acid contact parts after chemical oxidation treatment in the above solution, let it stand at room temperature for 12 hours, then take it out, rinse it with anhydrous ethanol three times, and dry it for later use.
[0070] S3. Dissolve 0.5 g of 2-methylimidazole and 0.2 g of zinc nitrate hexahydrate in 20 mL of deionized water, slowly drop the 2-methylimidazole solution into the zinc nitrate solution, stir thoroughly for 30 minutes, heat to 120°C and react for 24 hours. After the reaction is completed, cool to room temperature, collect the precipitate by centrifugation, wash it three times with deionized water and anhydrous ethanol respectively, and vacuum dry it for 12 hours to obtain a powder. Wash it three times with N,N-dimethylformamide and dry it for 12 hours to obtain powder A.
[0071] S4. Dissolve 0.5 g of acrylic acid and 0.01 g of azobisisobutyronitrile in 50 mL of anhydrous ethanol, react at 70°C for 6 hours under a nitrogen atmosphere, then cool to room temperature, collect the precipitate by centrifugation, wash it three times with anhydrous ethanol, and dry it for 12 hours to obtain powder B.
[0072] S5. Disperse 0.1 g of powder A obtained from S3 and 0.1 g of powder B obtained from S4 in 50 mL of N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes, and add 50 mL of ethanol to obtain a slurry for corrosion protection coating of sulfuric acid contact parts.
[0073] S6. Spray the sulfuric acid contact part anti-corrosion coating slurry onto the surface of the sulfuric acid contact part, dry it at room temperature for 1 hour, put it into an oven, heat it to 80°C, and cure it for 2 hours.
[0074] Comparative Example 5
[0075] S1. Ultrasonic clean the stainless steel sulfuric acid contact parts with anhydrous ethanol and acetone for 10 minutes respectively to remove grease and impurities on the surface. Chemically oxidize the stainless steel sulfuric acid contact parts by soaking them in 10% sulfuric acid at room temperature for 10 minutes, rinse them with deionized water, and dry them for later use.
[0076] S2. Add 0.6 g of 3-aminopropyltriethoxysilane to 20 mL of anhydrous ethanol and stir until completely dissolved. Soak the sulfuric acid contact parts after chemical oxidation treatment in the above solution, let it stand at room temperature for 12 hours, then take it out, rinse it with anhydrous ethanol three times, and dry it for later use.
[0077] S3. Dissolve 0.5 g of 2-methylimidazole and 0.2 g of zinc nitrate hexahydrate in 20 mL of deionized water, slowly add the 2-methylimidazole solution dropwise to the zinc nitrate solution, stir thoroughly for 30 minutes, heat to 120 ° C and react for 24 hours. After the reaction is completed, cool to room temperature, collect the precipitate by centrifugation, wash it with deionized water and anhydrous ethanol for 3 times, vacuum dry it for 12 hours to obtain powder, then disperse 0.1 g of the powder in 50 mL of N, N-dimethylformamide, ultrasonically treat it for 30 minutes, then add 0.05 g of 3-aminopropyltriethoxysilane, continue ultrasonic treatment for 1 hour, wash it with N, N-dimethylformamide 3 times and dry it for 12 hours to obtain modified powder A.
[0078] S4. Dissolve 0.5 g of acrylic acid and 0.01 g of azobisisobutyronitrile in 50 mL of anhydrous ethanol, react at 70°C for 6 hours under a nitrogen atmosphere, then cool to room temperature, collect the precipitate by centrifugation, wash it three times with anhydrous ethanol, and dry it for 12 hours to obtain powder B.
[0079] S5. Disperse 0.1 g of modified powder A obtained from S3 and 0.2 g of powder B obtained from S4 in 50 mL of N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes, add 50 mL of ethanol, and obtain a slurry for corrosion protection coating of sulfuric acid contact parts.
[0080] S6. Spray the sulfuric acid contact part anti-corrosion coating slurry onto the surface of the sulfuric acid contact part, dry it at room temperature for 1 hour, put it into an oven, heat it to 80°C, and cure it for 2 hours.
[0081] The performance test of the sulfuric acid contact parts of the embodiment and the comparative example was carried out. Each contact part was completely immersed in 89% sulfuric acid, and an electrochemical corrosion test was carried out using a three-electrode electrochemical cell system at 60°C to detect the corrosion potential. The weight gain after corrosion was measured by placing the sulfuric acid contact parts under 89% sulfuric acid conditions, at a detection temperature of 60°C, for 30 days, and comparing the mass changes of the pipelines before and after corrosion. The porosity was measured using a porosity tester.
[0082]
[0083] Comparative Example 1 did not use 3-aminopropyltriethoxysilane for immersion, and it can be seen that its porosity was significantly increased. Comparative Example 2 did not add modified powder A, and it can be seen that its anti-corrosion effect was significantly reduced. Comparative Example 3 did not add powder B, and the anti-corrosion effect also decreased. In Comparative Example 4, powder A was not modified, the porosity was greatly increased, and the corrosion weight gain was also increased. In Comparative Example 5, the ratio of modified powder A and powder B was changed, and the amount of powder B was increased, and it can be seen that its anti-corrosion effect was significantly reduced.
Claims
1. A process for preparing an anti-corrosion coating for sulfuric acid contact parts, characterized in that: The following steps are involved: S1. Perform chemical oxidation treatment on the sulfuric acid contact parts and soak them in the treatment solution at room temperature for 10-20 minutes; S2. Add 3-aminopropyltriethoxysilane to anhydrous ethanol and stir until completely dissolved. Soak the sulfuric acid contact parts after chemical oxidation treatment in the above solution, let it stand at room temperature for 12-16 hours, take it out, and rinse it with anhydrous ethanol for later use. S3, dissolving 2-methylimidazole and zinc nitrate hexahydrate in deionized water respectively, slowly adding the 2-methylimidazole solution to the zinc nitrate solution, stirring for 30-40 minutes, heating to 100-120°C for reaction for 20-24 hours, cooling to room temperature after the reaction, collecting the precipitate by centrifugation, washing with deionized water and anhydrous ethanol respectively, vacuum drying for 12-16 hours to obtain a powder, and then dispersing the powder in N,N-dimethylformamide, ultrasonically treating for 30-40 minutes, and then adding 3-aminopropyltriethoxysilane, continuing ultrasonic treatment for 1-2 hours, washing with N,N-dimethylformamide and drying for 12-16 hours to obtain a modified powder A; S4, dissolving acrylic acid and azobisisobutyronitrile in anhydrous ethanol, reacting for 5-7 hours at 65-75° C. in a nitrogen atmosphere, cooling to room temperature, collecting the precipitate by centrifugation, washing with anhydrous ethanol and drying for 12-16 hours to obtain powder B; S5. Disperse the modified powder A obtained in S3 and the powder B obtained in S4 in N,N-dimethylformamide, wherein the weight ratio of the modified powder A to the powder B is 1-3:1, subject to ultrasonic treatment for 30-50 minutes, add ethanol to obtain an anti-corrosion coating slurry for sulfuric acid contact parts, spray the anti-corrosion coating slurry for sulfuric acid contact parts onto the surface of the sulfuric acid contact parts, dry at room temperature for 1-2 hours, place in an oven, heat to 70-90°C, and cure for 2-4 hours to obtain an anti-corrosion coating for sulfuric acid contact parts.
2. The process for preparing the anti-corrosion coating for sulfuric acid contact parts according to claim 1, characterized in that: The sulfuric acid contact parts were pretreated by ultrasonic cleaning with anhydrous ethanol and acetone for 10-20 minutes respectively.
3. The process for preparing the anti-corrosion coating for sulfuric acid contact parts according to claim 1, characterized in that: The treatment liquid in step S1 is one or more of hydrochloric acid, sodium hydroxide, sulfuric acid or nitric acid, with a concentration of 5%-10%.
4. The process for preparing the anti-corrosion coating for sulfuric acid contact parts according to claim 1, characterized in that: The concentration of the 3-aminopropyltriethoxysilane solution in step S2 is 0.07-0.15 mol / L.
5. The process for preparing the anti-corrosion coating for sulfuric acid contact parts according to claim 1, characterized in that: The concentration of the 2-methylimidazole solution in step S3 is 0.25-0.35 mol / L, and the concentration of the zinc nitrate solution is 0.02-0.05 mol / L.
6. The process for preparing the anti-corrosion coating for sulfuric acid contact parts according to claim 1, characterized in that: The mass ratio of the powder and 3-aminopropyltriethoxysilane in step S3 is 2-5:
1.
7. The process for preparing the anti-corrosion coating for sulfuric acid contact parts according to claim 1, characterized in that: The mass ratio of acrylic acid to azobisisobutyronitrile in step S4 is 45-55:
1.
8. The process for preparing the anti-corrosion coating for sulfuric acid contact parts according to claim 1, characterized in that: The spraying thickness of the sulfuric acid contact part anti-corrosion coating slurry is 10-30 μm.
Citation Information
Patent Citations
High-adhesive-force anti-corrosion epoxy coating as well as preparation method and use method thereof
CN117757333A
Surface coating for degradable magnesium and magnesium alloys and method for preparing the same
US20230212755A1